UJI MUTU VIRGIN COCONUT OIL (VCO) DENGAN METODE FERMENTASI DAN PEMANCINGAN - A Tenriugi Daeng Pine; Khusnul Khatimah (Jurnal Kesehatan Yamasi Makassar, 2024)
Quality test research has been carried out with the aim of knowing the physical quality of VCO preparations made using hybrid coconut. The research method used was laboratory experimental by conducting physical quality tests on preparations carried out at the Natural Materials Technology Laboratory and Pharmaceutical Chemistry Laboratory at the Yamasi Pharmacy Academy, Makassar. Hybrid coconut is made in the form of coconut cream then the cream is made into VCO preparations using two methods, namely the fermentation method and the fishing method. The physical quality tests carried out included organoleptic tests, water content, free fatty acids and peroxide numbers. The results of this study stated that from the two methods of making VCO, the baiting method gave better results than the fermentation method, namely the fishing method produced a yield of 41.4% , organoleptic (specific smell of coconut aroma, typical taste of coconut oil and clear color) water content of 0.049%, free fatty acids 0.1% and peroxide value 10.8 mg ek/k. Whereas the fermentation method produced a yield of 29.3%, organoleptic (typical coconut aroma, distinctive coconut oil taste and clear color), 0.029% water content, 0.45% free fatty acids and 4.2 mg oak/k peroxide.